A Language Index of Grammatical Gender Dimensions to Study the Impact of Grammatical Gender on the Way We Perceive Women and Men - Gygax, Pascal Mark; Elmiger, Daniel; Zufferey, Sandrine; Garnham, Alan; Sczesny, Sabine; von Stockhausen, Lisa; Braun, Friederike; Oakhill, Jane (Frontiers in Psychology, 2019)
Psycholinguistic investigations of the way readers and speakers perceive gender have shown several biases associated with how gender is linguistically realised in language. Although such variations across languages offer interesting grounds for legitimate cross-linguistic comparisons, pertinent characteristics of grammatical systems – especially in terms of their gender asymmetries – have to be clearly identified. In this paper, we present a language index for researchers interested in the effect of grammatical gender on the mental representations of women and men. Our index is based on five main language groups (i.e., grammatical gender languages, languages with a combination of grammatical gender and natural gender, natural gender languages, genderless languages with few traces of grammatical gender and genderless languages) and three sets of specific features (morphology, masculine-male generics and asymmetries). Our index goes beyond existing ones in that it provides specific dimensions relevant to those interested in psychological and sociological impacts of language on the way we perceive women and men. We also offer a critical discussion of any endeavour to classify languages according to grammatical gender.